MODELING PURCHASING DECISIONS : COMPETITIVE STRATEGIES OF LOCAL COFFEE SHOP BRANDS IN BALI - Purnama Sari, Desak Made Febri; Pradipta Arba, Ida Bagus Agung Rama; Manik Parasari, Nyoman Sri; Oka Martini, Ida Ayu (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This research discusses the phenomenon of how consumers choose coffee shops and how local brand coffee shops compete with national coffee shops. This trend shows that more and more na-tional brand coffee shops are entering Bali and how local brand coffee shops compete with their advantages. Therefore, this research aims to model purchasing decisions: the competitive strategy of local coffee shop brands in Bali. Thelresearch methodlused was quantitative data analysis with 252 consumers who made transactions at three local brand coffee shops in Bali. The data was analyzed using Confirmatory Factor Analysis (CFA) in the SPSS version 25 program. The results of the data analysis showed that from the 40 indicators that were initially tested, two main factors were formed that could explain the decision to purchase local coffee shop brands in Bali, namely "Brand immersion and Value Proposition" The results of this research indicate that these factors play an important role in understanding the reasons for consumer purchasing decisions in order to optimize the competitive strategy of local coffee shop brands in Bali. Therefore, these factors can be used as a basis for optimizing marketing and service strategies for local brand coffee shop business actors in Bali.